Pengaruh Media Pembelajaran Terhadap Kemandirian Belajar dan Keterampilan Menulis Teks Drama - Razanah, Marini; Solihati, Nani; Safi'i, Imam (Program Studi Pendidikan Bahasa Program Pascasarjana Universitas Negeri Jakarta, 2024)
Students' ability in writing drama text is influenced by several factors that occur in learning. The purpose of the study was to determine the effect of learning media and students' independence in learning on the skills of writing drama texts of students in class XI of SMAN 21 East Jakarta. This research used experimental method. The population in this study were all students of class XI of SMAN 21 East Jakarta. The research sample was conducted using Purposive Sampling technique as many as 60 students who were divided into two groups, where 30 students learned using family movie drama media and the other 30 people learned using conventional media. The instruments used in this study are: Learning independence questionnaire and drama text writing skill test. The results showed that the use of family film drama media gave better results in the aspects of learning independence and drama text writing skills. The use of conventional media makes students learn through several stages or indirectly. The use of family film drama media is recommended in learning to write drama texts because it can provide a direct picture and increase students' learning independence and motivation